2022
DOI: 10.3389/fimmu.2022.997985
|View full text |Cite
|
Sign up to set email alerts
|

Largemouth bass (Micropterus salmoides) exhibited better growth potential after adaptation to dietary cottonseed protein concentrate inclusion but experienced higher inflammatory risk during bacterial infection

Abstract: Cottonseed protein concentrate (CPC) has been proven to partially replace fishmeal without adverse effects on fish growth performance, while little information is known about the effects on liver health during bacterial infection. In the present study, 15% CPC was included into the diet of juvenile largemouth bass (32.12 ± 0.09g) to replace fishmeal for 8 weeks, with fish growth potential and hepatic inflammatory responses during Nocardia seriolae (N. seriolae) infection systemically evaluated. After adaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…In the normal fish liver, hepatocytes were double-layered and radially arranged around the central vein in bundles, with the vascular (sinusoids) and biliary (canaliculi) network distributed in the lacunae among hepatocytes. This is consistent with normal largemouth bass liver morphology reported in our previous study [ 25 ] and other studies [ 30 ]. Ammonia exposure has been reported to impair the histological features of Nile tilapia liver tissue [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the normal fish liver, hepatocytes were double-layered and radially arranged around the central vein in bundles, with the vascular (sinusoids) and biliary (canaliculi) network distributed in the lacunae among hepatocytes. This is consistent with normal largemouth bass liver morphology reported in our previous study [ 25 ] and other studies [ 30 ]. Ammonia exposure has been reported to impair the histological features of Nile tilapia liver tissue [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…Water parameters in the circulating water system were kept constant with the flow at 0.5 L/min and temperature at 26 ± 2 °C. Fish were fed with a diet (crude protein of 47.35%) reported in our previous study [ 25 ]. The water pH was maintained at 7.6 ± 0.2, and the dissolved oxygen was maintained at 7.5 ± 0.3 mg/L.…”
Section: Methodsmentioning
confidence: 99%
“…[ 70 ]. Mengya et al [ 71 ] showed that adding cottonseed protein to the diet of largemouth bass increased the risk of inflammation. Li et al [ 72 ] showed that adding soybean meal to a turbot diet caused intestinal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Largemouth bass ( Micropterus salmoides ) is globally recognized as one of the most economically significant fish species in aquaculture ( 1 ). It was introduced into China in the 1980s and has expanded to become a significant economic fish in China’s freshwater aquaculture industry ( 2 ).…”
Section: Introductionmentioning
confidence: 99%